Vocação e crise profética: uma leitura pastoral a partir de Jeremias 20.7-12 - Pontes, Edimilton de Carvalho (2011)
This research is related to the biblical field, with emphasis on the prophetic vocation and the crisis centered on Jeremiah, especially in the text Jr 20.7-12. The proposal is to apprehend important aspects about the crisis and the calling of the prophet for the purpose of pastoral practice in present days. The paper examines the issues involved in prophetic calling in order to understand the prophet and his mission of proclaiming the God s Word in compliance with his calling. It also tries to understand the crisis in prophet Jeremiah s life as a formative element of prophetic and thus also pastoral identity, starting with his confessions. It tries to come to grips with these fundamental concepts, in order to obtain the knowledge needed for the every day pastoral ministry.